The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1021/om030240y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Catalytic Properties of Constrained Geometry Cyclopentadienyl-phenoxytitanium Dichlorides

Abstract: The synthesis of four new bidentate ligands, 2-(3,4-diphenylcyclopentadienyl)-6-phenylphenol ((DCPP)H2, 7), 2-(3,4-diphenylcyclopentadienyl)-6-tert-butylphenol ((DCBP)H2, 8), 2-(3,4-diphenylcyclopentadienyl)-4, 6-di-tert-butylphenol (DCDBP)H2, 9), and 2-(3,4-diphenylcyclopentadienyl)-6-methylphenol ((DCMP)H2, 10), as well as their corresponding constrained geometry cyclopentadienyl-phenoxytitanium dichlorides ((DCPP)TiCl2 (11), (DCBP)TiCl2 (12), (DCDBP)TiCl2 (13), and (DCMP)TiCl2 (14)), are described. Complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…Adequately bulky ligand would weaken the interaction between the cationic catalyst and the anionic cocatalyst [16,35], therefore could favor the coordination of the olefins and increase the catalytic activity of the catalyst. Similar results have previously been observed for ethylene/1-hexene copolymerization reaction with other half-metallocene titanium(IV) catalyst systems [19,40,41]. With 9/ TIBA/B catalyst system, copolymerization experiments with different 1-hexene feed concentrations were carried out and obvious comonomer effect was observed.…”
Section: Copolymerization Of Ethylene With 1-hexenesupporting
confidence: 85%
“…Adequately bulky ligand would weaken the interaction between the cationic catalyst and the anionic cocatalyst [16,35], therefore could favor the coordination of the olefins and increase the catalytic activity of the catalyst. Similar results have previously been observed for ethylene/1-hexene copolymerization reaction with other half-metallocene titanium(IV) catalyst systems [19,40,41]. With 9/ TIBA/B catalyst system, copolymerization experiments with different 1-hexene feed concentrations were carried out and obvious comonomer effect was observed.…”
Section: Copolymerization Of Ethylene With 1-hexenesupporting
confidence: 85%
“…It is possible that excessive Al( i Bu) 3 would consume some of Ph 3 C þ BðC 6 F 5 Þ À 4 , which results in that the catalyst could not be efficiently activated [15]. It is also worth noting that the less active catalyst 3 gives higher molecular weight polyethylene, which could be explained by that the slow chain propagation in 3 will ensure to have sufficient monomer to coordinate to the catalyst metal center and thus suppress the chain termination through b-H elimination [11].…”
Section: Ethylene Polymerization Studiesmentioning
confidence: 99%
“…Reports concerning oxygen donor substituted cyclopentadienyl chromium catalysts are scarce. Previously, we demonstrated that phenoxy substituted cyclopentadienyl titanium complexes (e and f in Chart 2) are good catalysts for ethylene polymerization [11,12]. In this paper, we report the synthesis and characterization of two oxygen donor substituted cyclopentadiene ligands 1-(2-methoxyphenyl)-3,4-diphenylcyclopentadiene (1) and 1-(2-methoxyphenyl)-2,3,4,5-tetramethylcyclopentadiene (2), and their chromium complexes g 5 -1-(2-methoxyphenyl)-3,4-diphenylcyclopentadienylchromium dichloride (3) and g 5 -1-(2-methoxyphenyl)-2,3,4,5-tetramethylcyclopentadienylchromium dichloride (4), as well as the catalytic performance of complexes 3 and 4 for ethylene polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Reaction of TiCl 4 with the corresponding dilithio salts 2-(3,4-diphenylcyclopentadienyl)-6-phenylphenol derivatives gives the corresponding constrained geometry complexes. 188 Treatment of TiCl 4 with one equivalent of a 2-tetramethylcyclopentadienyl phenol derivative to give a coordination intermediates, followed by treatment with 2 equivalent of n-BuLi at low temperature gives tetramethylcyclopentadienylphenoxytitanium dichlorides in moderate yields. 189 Treatment of Ti(CH 2 Ph) 4 with 2-(tetramethylcyclopentadienyl)-4-methylphenol at 60 • in toluene cleanly gives (η 1 -OC 6 H 3 (CH 3 )-η 5 -C 5 Me 4 )Ti(CH 2 Ph) 2 (43).…”
Section: Ti CLmentioning
confidence: 99%
“…190 Several of the cyclopentadienylphenoxytitanium datives have been structurally characterized by single-crystal X-ray diffraction and the Cp(cent)-Ti-O angle in all cases was found to be approximately 107 • . [188][189][190] The analogous indenyl-phenoxytitanium complexes have recently been reported, and structurally characterized, with the Ind(cent)-Ti-O angle of approximately 105 • . Treatment of Ti(NMe 2 ) 4 with one equivalent 2-(inden-3-yl)-4,6-di-tert-butylphenol and its 1,2-di-Me, 2,4,7-tri-Me, and 1,2,4,7-tetra-Me derivatives gives the corresponding bis(dialkylamido) complexes such as, [Ti(η 1 -OC 6 H 2 {η 5 -Ind}-2-Bu t 2 -4,6)(NMe 2 ) 2 ].…”
Section: Ti CLmentioning
confidence: 99%